Peningkatan Keterampilan Membaca Puisi dengan Menggunakan Media Video pada Peserta Didik Kelas X UPT SMA Negeri 4 Sidrap - Rahmah, Siti; Khalik, Suhartini; Zain, Suardi (Nuances of Indonesian Language, 2023)
This research describes improving poetry reading skills using video media for UPT students at SMA Negeri 4 Sidrap. This research aims to: (1) determine the increase in teacher activity in learning to read poetry using video media, (2) determine the increase in student activity in learning to read poetry using video media, and (3) to determine the increase in poetry reading skills using video media for students. The subject of this study was class X IPA 1 UPT SMA Negeri 4 Sidrap, which consisted of 28 students. This type of research is classroom action research (CAR) using the Kurt Lewin model which consists of three action cycles. Data collection techniques are obtained from observation, interviews, tests and documentation. The results of this classroom action research were obtained by showing: (1) teacher activities in using video media in improving students' poetry reading skills in cycle I obtained a score of 66.66% in the good category, cycle II experienced an increase with a score of 72.91% in the good category, and in cycle III they got a score of 85.41% in the very good category, (2) students' activities in learning to read poetry using video media increased from cycle I got a score of 63.77% in the fair category, cycle II got a score of 71.16% good category, and in cycle III obtained a score of 78.43% in the good category, and (3) the results of improving students' poetry reading skills using video media in cycle I obtained a score of 46.42% in the poor category, cycle II experienced an increase with a score of 60 .71% in the sufficient category, and in cycle III there was an increase with a score of 82.14% in the very good category. The conclusion in this research is that learning Indonesian in poetry reading skills using video media can improve the quality of learning, namely increasing teacher skills, student activities and students' skills in reading poetry.